2015
DOI: 10.3389/fmicb.2015.00176
|View full text |Cite
|
Sign up to set email alerts
|

Detection of inhibitors of Candida albicans Cdr transporters using a diS-C3(3) fluorescence

Abstract: Candida albicans is a major cause of opportunistic and life-threatening, systemic fungal infections. Hence new antifungal agents, as well as new methods to treat fungal infections, are still needed. The application of inhibitors of drug-efflux pumps may increase the susceptibility of C. albicans to drugs. We developed a new fluorescence method that allows the in vivo activity evaluation of compounds inhibiting of C. albicans transporters. We show that the potentiometric dye 3,3′-dipropylthiacarbocyanine iodide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
23
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 24 publications
(25 citation statements)
references
References 33 publications
2
23
0
Order By: Relevance
“…In our previous investigations, we observed different influences on the Cdr1 transporter when combinations of FLC-beauvericin and diS-C3(3)-beauvericin were applied in which beauvericin was an inhibitor of the ABC transporters and diS-C3(3) was the substrate for these pumps [44]. Similar differences in inhibitory activity were observed for curcumin [45], the modulatory effect of which was restricted to R6G or miconazole, while it had no effect on the efflux of FLC.…”
Section: Discussionsupporting
confidence: 56%
“…In our previous investigations, we observed different influences on the Cdr1 transporter when combinations of FLC-beauvericin and diS-C3(3)-beauvericin were applied in which beauvericin was an inhibitor of the ABC transporters and diS-C3(3) was the substrate for these pumps [44]. Similar differences in inhibitory activity were observed for curcumin [45], the modulatory effect of which was restricted to R6G or miconazole, while it had no effect on the efflux of FLC.…”
Section: Discussionsupporting
confidence: 56%
“…We previously demonstrated that beauvericin inhibits multidrug efflux in S. cerevisiae, and a recent study suggests that beauvericin inhibits the C. albicans ABC transporters Cdr1 and Cdr2 (22,29). To determine whether beauvericin potentiates azole activity via inhibition of multidrug efflux in C. albicans, we assessed the drug synergy against strains lacking the ABC transporter genes CDR1 and CDR2 both individually and in combination.…”
Section: Resultsmentioning
confidence: 99%
“…Screens for inhibitors can be based on yeast growth measurements that demonstrate the reversal of fungal resistance to a pump substrate such as the azoles (chemosensitization) or can utilize the fluorescent properties of certain pump substrates such as rhodamine 6G (R6G) [54,74,75], Nile Red [76] or diS-C3 [77]. However, as noted above, growth chemosensitization assays, unless targeted to counter efflux-mediated resistance, may identify interference with one or more different aspects of resistance, not necessarily involving efflux.…”
Section: Screening Methods To Identify Inhibitors Of Fungal Efflux Pumpsmentioning
confidence: 99%